Diversity, distribution and ecology of dragonflies (odonata) from the Pampa biome in Rio Grande do Sul, Brazil - Renner, Samuel (2019)
This thesis is divided in interrelated but stand-alone chapters. The overlap in the text content between chapters has been kept to a minimum. However, there is some common material presented, particularly at the introductions of the chapters, methods and references. All chapters are published, submitted to scientific journals or manuscripts in development. Although Univates has its own standard format for submission of academic papers, the present thesis, except for chapter one and chapter seven (which obeys the format of Univates), meets the specific standards of each journal. The manuscripts presented in this thesis follow a chronological order, therefore the data (sampling sites) in each subsequent document is increased following the period of development of the studies. Chapter one presents a general introduction to the main topics studied, a general presentation of the study area and the overall structuring of the thesis. The following chapters,present each, a manuscript already published, in editorial process or submitted. Chapter two brings the first results from our sampled areas, through a species inventory, showing detailed data on the composition of the odonate communities of the Pampa and several new species records for the state. Chapter three is our first analyses development, using the dataset acquired in the field in comparison to features on the landscape of the Pampa, denoting the variability in the odonate assemblies in relation do the land cover they are within. Chapter four is a specific study, aiming to comprehend how dense are the communities in terms of rare and common species and how the common species, through niche occupation, affect negatively the presence of the rare species. The fifth chapter is based in an ecoregion approach, which has been developed following the tree cover and vegetation density. We explore how the Odonata assemblages differ from ecoregion to ecoregion, demonstrating their specificity to their environments. Chapter six consists in a first attempt to define odonates as bio indicators for the Pampa biome, testing a combination of two popular selection methods. And the last chapter (seven) is dedicated to a general discussion on the main findings of this study and the future works that could be developed. By the end of this document, as an appendix, are presented the prints of publications, submission, and co-authored papers produced during the doctoral period.